a et b et c sont des Nombres réels deux par deux différent montre que 1/(a-b)(a-c)+1/(b-c)(b-a)+1/(c-a)(c-b)=0 montre que
a+b/(b-c)(c-a)+(b+c)/(c-a)(a-b)+(a+c)/(b-a)(b-c) la reponse de la premiere question est ici http://nosdevoirs.fr/devoir/131618

1

Réponses

  • Utilisateur Brainly
2013-09-29T19:27:23+02:00
1/ (a-b)(a-c)+1/(b-c)(b-a)+1/(c-a)(c-b)
=
1/ (a-b)(a-c)-1/(b-c)(a-b)+1/(a-c)(b-c)
=(b-c)/ ((a-b)(a-c)(b-c))-(a-c)/((a-b)(a-c)(b-c)+(a-b)/((a-b)(a-c)(b-c)
=(b-c-a+c+a-b) ((a-b)(a-c)(b-c)
=0